2011
DOI: 10.1007/s13280-011-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate Warming and Pikeperch Year-Class Catches in the Baltic Sea

Abstract: Climate change scenarios concerning the Baltic Sea predict increase in surface water temperatures. Pikeperch (Sander lucioperca (L.)) inhabits the coastal areas of the northern Baltic Sea and is an important fish species for the Finnish fisheries. The year-class strength of pikeperch varies strongly between years and significantly depends on water temperature. We aimed to study the effects of changing temperature conditions on pikeperch fisheries and distribution based on commercial catch data from the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 38 publications
4
38
1
Order By: Relevance
“…In line with previous studies (Kjellman et al 2003;Lappalainen et al 2003;Pekcan-Hekim et al 2011), we found a positive relationship between pikeperch YCS and temperature. This result, as well as the strong and weak year classes corresponded to previous studies (Finnish Game and Fisheries Research Institute 2006;Pekcan-Hekim et al 2011).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In line with previous studies (Kjellman et al 2003;Lappalainen et al 2003;Pekcan-Hekim et al 2011), we found a positive relationship between pikeperch YCS and temperature. This result, as well as the strong and weak year classes corresponded to previous studies (Finnish Game and Fisheries Research Institute 2006;Pekcan-Hekim et al 2011).…”
Section: Discussionsupporting
confidence: 93%
“…This result, as well as the strong and weak year classes corresponded to previous studies (Finnish Game and Fisheries Research Institute 2006;Pekcan-Hekim et al 2011). Also the increases and decreases in the commercial pikeperch fishing catches were rather similar to those recorded from the Finnish Archipelago Sea (Lappalainen et al 2002;Heikinheimo et al 2006;PekcanHekim et al 2011).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations